Host Genetic Risk Factors for Chlamydia trachomatis-Related Infertility in Women. (16th August 2021) - Zheng, Xiaojing; Zhong, Wujuan; O'Connell, Catherine M; Liu, Yutong; Haggerty, Catherine L; Geisler, William M; Anyalechi, Gloria E; Kirkcaldy, Robert D; Wiesenfeld, Harold C; Hillier, Sharon L; Steinkampf, Michael P; Hammond, Karen R; et al.
Abstract: Background: Chlamydia trachomatis ( Ct ) infection ascending to the upper genital tract can cause infertility. Direct association of genetic variants as contributors is challenging because infertility may not be diagnosed until years after infection. Investigating the intermediate trait of ascension bridges this gap. Methods: We identified infertility genome-wide association study (GWAS) loci using deoxyribonucleic acid from Ct- seropositive cisgender women in a tubal factor infertility study and Ct -infected cisgender women from a longitudinal pelvic inflammatory disease cohort with known fertility status. Deoxyribonucleic acid and blood messenger ribonucleic acid from 2 additional female cohorts with active Ct infection and known endometrial infection status were used to investigate the impact of infertility single-nucleotide polymorphisms (SNPs) on Ct ascension. A statistical mediation test examined whether multiple infertility SNPs jointly influenced ascension risk by modulating expression of mediator genes. Results: We identified 112 candidate infertility GWAS loci, and 31 associated with Ct ascension. The SNPs altered chlamydial ascension by modulating expression of 40 mediator genes. Mediator genes identified are involved in innate immune responses including type I interferon production, T-cell function, fibrosis, female reproductive tract health, and protein synthesis and degradation. Conclusions: We identified Ct- related infertility loci and their potential functional effects on Ct ascension.